POLITICAL, SOCIAL, PSYCHOLOGICAL AND HISTORICAL CONSCIOUSNESS IN DILAWAR FIGAR'S POETRY - Muhammad Fiaz Akbar; Dr. Muhammad Mumtaz Khan Kalyani (Zaban-o-Adab, 2022)
Dilawar Fagaar is a famous comic poet of Urdu literature. He was born 8th July 1929, and died 21 January 1998 in Karachi. In this research article, I have tried to highlight the political, Social, Psychological and historical consciousness in the poetry of Dilawar Fagar. In this research article, I have used his primary books, books and critical books written on Dilawar Fagar.